Asthma mortality in children and adolescents of Brazil over a 20-year period - Raquel Reis Pitchon (Jornal de Pediatria, 2020)
Objective: To evaluate the number of asthma deaths and the temporal trend of the asthma-specific mortality rate in children and adolescents up to 19 years of age in Brazil. Methods: This is an ecological time-series study of asthma deaths reported in Brazil, in the population up to 19 years of age, between 1996 and 2015. The specific asthma mortality rate and its temporal trend were analyzed. Results: There were 5014 deaths during the 20 years evaluated, with the majority, 68.1%, being recorded in children under 5 years of age. The specific asthma mortality rate ranged from 0.57/100,000 in 1997 to 0.21/100,000 in 2014, with a significant reduction of 59.8%. Regarding the place of death, 79.4% occurred in a hospital setting. In this sample, the adolescents had a 1.5-fold higher chance of death out-of-hospital than children up to nine years of age. There was no significant difference in the temporal trend between the genders and no significant decrease in out-of-hospital deaths. Conclusions: This study found a temporal trend for a reduction in asthma deaths over 20 years in children and adolescents in Brazil. Mortality rates varied across the geographic regions of the country and were higher in the Northeast. The prevalence of deaths under 5 years of age may be associated with the greater vulnerability of this age group in low-income countries. In adolescence, deaths outside the hospital environment are noteworthy. Asthma deaths are rare but unacceptable events, considering the treatable nature of the disease and the presence of avoidable factors in most of fatal outcomes. Resumo: Objetivo: Estimar o número de óbitos por asma e a tendência temporal da taxa de mortalidade por asma em crianças e adolescentes no Brasil. Métodos: Estudo ecológico de séries temporais em que foram avaliados os óbitos por asma ocorridos no Brasil entre 1996 e 2015, na população com até 19 anos. Foram analisadas a taxa de mortalidade específica por asma e a sua tendência temporal. Resultados: Ocorreram 5.014 óbitos, a maioria (68,1%) registrada em menores de cinco anos. Observou-se uma oscilação da taxa de mortalidade específica por asma entre 0,57 e 0,21/100.000 habitantes, o que correspondeu a uma redução de 59,8% no período. Quanto ao local dos óbitos, 79,4% ocorreram em ambiente hospitalar. Nesta amostra o adolescente teve 1,5 vez mais chance de óbito por asma fora do ambiente hospitalar do que as crianças até nove anos. Não foi observada diferença significativa da redução da tendência temporal entre os sexos e dos óbitos fora do ambiente hospitalar. Conclusões: Houve tendência temporal de redução da mortalidade por asma em crianças e adolescentes nos 20 anos avaliados. As taxas de mortalidade variaram nas diversas regiões geográficas do país, foram mais elevadas na Região Nordeste. O predomínio dos óbitos abaixo de cinco anos pode se associar a maior vulnerabilidade desse grupo em países de baixa renda. Na adolescência, ressaltam-se óbitos fora do ambiente hospitalar. As mortes por asma são eventos inaceitáveis, considera-se o caráter tratável da doença e a presença de fatores evitáveis na maioria dos desfechos fatais.